Assesment of Improved Chullah in Rural Settings of Hisar - Chauhan, Komal; Singh, Kiran; Rani, Nigam (Indian Journal of Extension Education, 2021)
Rural population in India depends on traditional chullah for the cooking purpose. TheyÂ depend on biomass inputs since it is obtainable free of cost. This practice can be harmful to the respiratory health of human beings, as well as contribute to climate change. TheÂ present study was conducted on 30 households of adopted village Budak of Hisar district under NASF- ICAR project. An observation sheet was used to collect the data regarding health effects of traditional chullah and impact of improved chullah. Study found the variousÂ health related problems viz: irritation in eyes, respiratory problems, backache, low visibility, headache etc. faced by the respondents while using traditional chullah. Irritation in eyesÂ was the most reported problem by the respondents as it got highest mean score (2.6 andÂ Ist rank). Average saved time in preparing the meal by the improved chullah was 13.16 minutes and technical benefits got first rank (overall mean score 2.9). Improved chullahÂ could save biomass input, human health and environment by reducing the time in cooking and creating less smoke or no smoke while cooking.